A new analysis method for structural failure evaluation. (October 2015) - Estêvão, João M.C.; Oliveira, Carlos Sousa
Highlights: The new Fibre Contact Element Method (FCEM) is presented. FCEM errors were evaluated for linear problems. The FCEM results were compared with analytical solutions. Results indicate that the ultimate load of a structure can be obtained with the FCEM. Abstract: There are many possible approaches for structural failure evaluation which uses different nonlinear structural analysis methods. For computer implementation purposes, some important differences between them are the results precision, the amount of computer memory needed and computer processing time. For solving practical problems, a compromise between accuracy and computational effort is needed. In this work, a new method is presented for linear and nonlinear structural analysis. The new developed method was named Fibre Contact Element Method (FCEM). In the proposed method, structures are divided in a mesh of several small rectangular block elements (neighbour blocks do not need to be aligned). These elements are divided in several micro fibre elements. Fibres belonging to neighbour blocks are connected between contact points. Two degrees of freedom are considered per contact point and three degrees of freedom are considered for each block (in a 2D model). The elemental block stiffness matrix is obtained from the assembly of fibre stiffness matrix. A static matrix condensation is preformed to reduce the block stiffness matrix dimension. The elasticity and plasticity is concentrated on each fibre element. Global nonlinear response can result from flexural or from shear fibre cracking or yielding. In this work, comparisons between numerical and analytical results are presented. The new method seems to be accurate and fast enough for solving practical problems, namely for seismic damage assessment. Results seem to demonstrate that FCEM can be a valid option for using in structural failure evaluation.